COMPANY PROFITABILITY AND LIQUIDITY IMPACT ON TAX AGGRESSIVENESS: REACTIONS FROM MANUFACTURING COMPANIES IN NIGERIA - Adegbite, Tajudeen Adejare; MUSTAPHA, TAOHEED OLUREMI; Eleja, Fawaz Oyinlola; Ariyo Edu, Aminat Arike ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2025)
The impact of company liquidity and profitability on tax aggression in Nigerian consumer products listed manufacturing companies was investigated in this study. Ex-post facto research methodology was applied. The twenty manufacturing companies that were quoted on the Nigerian Stock Exchange between 2012 and 2023 made up the population. Data sourced from annual financial reports of chosen listed manufacturing companies in Nigeria analysed using the panel data regression technique, correlation Matrix, Variance Inflation Factor and the Hausman Test. The analysis revealed that firm liquidity, profitability, firm leverage all have positive insignificant correlation with tax aggressiveness, and working capital is negatively insignificant. Finally, dividend payroll has positive significance on tax aggressiveness. Conclusively, firm liquidity, firm profitability, firm leverage and working capital pose non-significant effect on tax aggressiveness but dividend payroll has a significant correlation with tax aggressiveness in quoted manufacturing companies in Nigeria. It is therefore recommended that companies' tax policy should prioritize asset expansion to generate greater value for the organization in order to judiciously manage their tax aggressiveness. Also, manufacturing firms should adopt a thorough liquidity management plan that takes into account both long-term financial goals and short-term financial requirements to avoid falling into illegal tax aggressiveness.